2008
DOI: 10.1073/pnas.0803657105
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection of FLT1 alleles and their association with malaria resistance in utero

Abstract: Placental malaria (PM) caused by Plasmodium falciparum contributes significantly to infant mortality in sub-Saharan Africa and is associated with pregnancy loss. We hypothesized that fetal genes that modify PM would be associated with fetal fitness. During PM, placental trophoblasts produce soluble fms-like tyrosine kinase 1 (sFlt1), also known as soluble VEGF receptor 1, an angiogenesis inhibitor associated with preeclampsia. Here we present a study examining the genotype of the fms-related tyrosine kinase 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…The importance of placental inflammation in malaria of pregnancy was recently reinforced by data suggesting that polymorphisms affecting expression of the FMS-like tyrosine kinase 1 (FLT1) gene, which encodes a receptor for VEGF (which can act as a proinflammatory cytokine), are under natural selection in this condition. In a study of Tanzanian mothers and infants (54), maternal genotypes of relatively increased FLT1 expression (as a result of homozygosity for short dinucleotide repeat polymorphisms in the 3′ untranslated region [i.e., SS dinucleotide repeat genotypes]) were associated with prior fetal losses in first-time mothers with placental malaria, and SS genotypes in the newborns of first-time mothers were linked to higher occurrences of low birth weight. Placentas delivered with the SS newborns also showed greater inflammation, as judged by histological findings and elevated levels of transcripts encoding IFN-γ and immunoglobulin heavy chains.…”
Section: Polymorphism Mitigating Placental Inflammation In Malaria Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of placental inflammation in malaria of pregnancy was recently reinforced by data suggesting that polymorphisms affecting expression of the FMS-like tyrosine kinase 1 (FLT1) gene, which encodes a receptor for VEGF (which can act as a proinflammatory cytokine), are under natural selection in this condition. In a study of Tanzanian mothers and infants (54), maternal genotypes of relatively increased FLT1 expression (as a result of homozygosity for short dinucleotide repeat polymorphisms in the 3′ untranslated region [i.e., SS dinucleotide repeat genotypes]) were associated with prior fetal losses in first-time mothers with placental malaria, and SS genotypes in the newborns of first-time mothers were linked to higher occurrences of low birth weight. Placentas delivered with the SS newborns also showed greater inflammation, as judged by histological findings and elevated levels of transcripts encoding IFN-γ and immunoglobulin heavy chains.…”
Section: Polymorphism Mitigating Placental Inflammation In Malaria Ofmentioning
confidence: 99%
“…Relatively decreased levels of VEGF-FLT1 signaling associated with genotypes containing long dinucleotide repeat polymorphisms (i.e., SL and LL genotypes) thus might confer increased fetal fitness in utero by reduced maternal inflammatory response to placental P. falciparum infection. Interestingly, a soluble form of FLT1 (sFlt1) that binds VEGF and antagonizes FLT1 signaling has been shown to be elevated in preeclampsia (55), raising the possibility of selection by malaria in the evolution of preeclampsia (54).…”
Section: Polymorphism Mitigating Placental Inflammation In Malaria Ofmentioning
confidence: 99%
“…In sub--Saharan Africa, malaria causes 20% of the cases of low infant birthweight, along with slow growth, spontaneous abortion, maternal anemia, and infant mortality [9,78,79]. Intriguingly, positive selection on a genetic variant of the gene FLT1, which reduces spontaneous abortions in cases of placental malaria, has been found for a malaria--endemic population in Tanzania [80]. This indicates that in the case of malaria resistance, selection mediated by pregnant women and their fetuses alone is sufficient for adaptive change in allele frequency in a population.…”
Section: Infectious Disease and Selection During Pregnancymentioning
confidence: 99%
“…In this issue of the PNAS, Muehlenbachs et al (7) provide evidence that a dinucleotide repeat polymorphism in the 3Ј UTR of the fms-like tyrosine kinase 1 (FLT1) gene may be under natural selection in malaria-endemic areas because of its effects on adverse outcomes of placental malaria. The authors have previously shown that elevated soluble Flt1 (sFlt1) is associated with chronic placental malaria and gestational hypertension in nulliparous women from the same population (8).…”
mentioning
confidence: 99%
“…Therefore, Flt1 and sFlt1 may have opposing effects on inflammation. The dinucleotide repeat polymorphism studied by Muehlenbachs et al (7) was shown to affect expression levels of Flt1 in cord blood monocytes: alleles with fewer than 28 repeats (S alleles) were associated with greater expression of Flt1 compared with alleles with 28 or more repeats (L alleles). Interestingly, SS fetal genotype was also associated with higher levels of sFlt1 in maternal plasma.…”
mentioning
confidence: 99%